ENGAGING STUDENTS IN 15-MINUTE SILENT READING IN ENGLISH CLASS: STUDENTS’ PERCEIVED BENEFITS - Khusnul Khotimah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Grounded from the input hypothesis proposed by Krashen in language learning, a plethora of studies has been addressed to investigate the role of extensive reading which is generally done as an outside classroom activity. However, the integration of similar activities as a part of teaching procedures in the classroom is inadequately explored. Therefore, to fill this lacuna, this article briefly chronicles the enactment of 15-minute silent reading as the adoption of extensive reading in an English class. 32 freshmen were recruited on a voluntary basis. Nested in action research, students engaged in five activities: 1) building knowledge and tutorial,2) material self-selection, 3) silent reading, 4) short sharing session, and 5) individual and collective reflection within 5 weeks of time frame. Findings from the classroom observations, students’ reflective journals, and oral collective reflection indicate that the participants responded positively and acknowledged some valuable benefits. Overall, the empirical evidence suggests that 15-minute silent reading can be one of alternative activities to be integrated in the classroom instruction.